The Social Function of the Neoliberal State: Hayek, Keynes, and the Contested Architecture of Market Order - Mohamed AIT BELA,; Hassan YAKOU, (African Scientific Journal, 2026)
Abstract This article examines the theoretical confrontation between Friedrich von Hayek and John Maynard Keynes over the social function of the state under capitalism. Drawing on primary texts and recent scholarship in political theory and political economy, it argues that Hayek's account of the minimal state rests on three interconnected tensions: an epistemic claim privileging market knowledge over collective deliberation; a conception of negative freedom that occludes the conditions of its own realization; and a theory of spontaneous order presented as naturally emergent despite being institutionally produced. Keynes's critique is reconstructed as a three-level challenge to the anthropological, macroeconomic, and epistemological presuppositions of the Hayekian framework. The article traces how post-1970s neoliberal governance inherited and amplified these contradictions, producing a social state that both dismantles and depends on welfare institutions. The debate is thus read not as a settled controversy but as a diagnostic resource for understanding the structural instabilities of contemporary neoliberal social policy. Keywords: Hayek; Keynes; neoliberalism; social state; epistemic argument; spontaneous order; social policy; political economy